SEJARAH PEMBANGUNAN BANDARA SILANGIT DAN PERKEMBANGANNYA DARI TAHUN 2005 – 2017 - Jones Harun Simanjuntak; Ridwan Melay; Tugiman MS Tugiman MS (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: In the beginning the airport just a empty area which is landed by planes as the wind direction or military business. At the world war I, the airport started to contruct permanently as while the improving of using of air transportation and connecting from one island to other island. To support the air transportation activity then they contructed a wide field as the place of plane landing and take off and now it called airport. It’s started when Japan collonial and used for Japan millitary business. The history of the Silangit name based on story from generation to generation and the historical fact still exist around airport. That name came up when the Japan collonial while lot of people from Pariksabungan villages was death because shooted by Japan soldier. Lots of mother loose their husband pouring their tears and pain while criying ont “Cross” in the sky. That the only one place to accusation because they were powerless, to fight back Japan soldier which just relying arrow. By its development, Silangit airport are truly needed for people from Siborong-borong district to Samosir district. The method that used is descriptive qualitative method which the data colleted through interview, observation,documentation and literature study. The data analysis done by qualitative formula.Key Words: Contraction and Development, Silangit airport, Siborongborong